Factors influencing the utilization of Focused antenatal care services during pregnancy, a study among postnatal women in a tertiary healthcare facility, Ghana - Kennedy Diema Konlan; Joel Afram Saah; Roberta Mensima Amoah; Abdul Razak Doat; Iddrisu Mohammed; Juliana Asibi Abdulai; Kennedy Dodam Konlan (Wiley, 2020)
Abstract Aim To assess the factors that influence the utilization of FANC services among pregnant women. Methodology A cross‐sectional quantitative study conducted among 210 postnatal women in Ho Teaching Hospital. Data were entered into Microsoft excel, cleaned and transported to SPSS and analysed. Cross tabulations were used to explore associations between variables. Results The respondents indicated that FANC would enable them to receive comprehensive ANC (74.8%). Higher parity was significantly associated with low utilization of FANC (p = .028). Long distance to the health facility, seeking permission to use FANC was significantly associated with low utilization of FANC (p < .001). Fear associated with witchcraft was associated with low FANC utilization (p < .001).